Anticipation in Families with Chronic Lymphocytic Leukemia and Other Lymphoproliferative Disorders - Awan, Haneef (Libertas Academica, 2010)
Fifty-one parent-offspring pairs with chronic lymphocytic leukemia (CLL) or other lymphoproliferative disorders (nonCLL) such as malignant lymphoma, multiple myeloma, or other types of lymphocytic leukemia than CLL were ascertained independently in 38 families. There were 30 CLL-CLL parent-offspring pairs and 21 pairs with nonCLL in parents and/or in offspring. The median age of onset of disease was 13 years lower in the offspring than in the parents when comparing all 51 pairs (P < 0.001). This difference was mainly caused by a significantly lower age at onset in offspring with parental nonCLL (P < 0.001) where paternal disease was transferred especially to sons, while affected offspring to parents with CLL have the same age at debut of disease than their parents (P = 0.130) and a nearly equal transfer to sons and daughters. The low-malignant follicular small B-cell lymphoma was the predominant diagnosis within nonCLL. Anticipation is pointed out as one likely mechanism behind the lower age at onset of disease in offspring than in parents, even if a part of this difference is ascribed to a generally earlier diagnosis with modern technology in offspring than in parents.